The effect of board of commissioners, audit committee, and stock ownership concentration on audit report lag of banking companies in Indonesia Stock Exchange - Ganang Setiawan; Joicenda Nahumury (The Indonesian Accounting Review, 2014)
This study aims to examine the effect of corporate governance characteristics such as board size, independence of the board of commissioners, the size of the audit committee, audit committee independence, audit committee competence, and concentration of stock ownership on audit report lag. In addition, this study also tests three control variables such as firm size, type of auditor, and profitability. One hundred and fiftysix sample of banking companies listed in the Indonesia Stock Exchange during the 6 years of the study were obtained by using purposive sampling technique. The results of multiple regression analysis proved that only board size variable that affects the audit report lag, while the other three control variables has no significant effect on audit report lag. This result suggested that auditors perform the audit more efficientlyand effectively, for BAPEPAM-LK and Bank Indonesia as regulator to review again the regulation about corporate governance, for the future researcher to be reference in developing research.